2017
DOI: 10.1177/1093526617693106
|View full text |Cite
|
Sign up to set email alerts
|

ALOX15 Immunohistochemistry Aids in the Diagnosis of Eosinophilic Esophagitis on Pauci-eosinophilic Biopsies in Children

Abstract: Histologically, esophageal biopsies should have ≥15 intraepithelial eosinophils (IEEs) per high power field (HPF) to support a clinicopathologic diagnosis of eosinophilic esophagitis (EoE). Children with clinically apparent EoE may show pauci-eosinophilic biopsies due to patchy involvement. Immunostaining (Immunohistochemistry) for arachidonate-15 lipooxygenase (ALOX15) has been demonstrated to be a sensitive marker for EoE. We retrospectively assessed the expression of ALOX15 in 48 biopsies from 21 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some researchers have Karamitopoulou et al, 2007;Farnebo et al, 2011;Omori et al, 2011;Sen et al, 2015;Heng et al, 2016;Bani-Ahmad et al, 2018;Chen et al, 2019;Henrich et al, 2019;Moledina et al, 2019;Schiffmann et al, 2019 Prognostic Bcl-2, Bax, p53, Fas, FasL, caspase-2, caspase-3, caspase-7, caspase-8, caspase-9, TNF-α, DNA fragmentation, Bak, Bok, Bim, PUMA, PMAIP1, MCL1, BCL2L10, TRAIL, TRAIL-R1/2/3, c-FLIP, IAPs Feng et al, 2018;Huang K.H. et al, 2018 Necroptosis Diagnostic NLRP3, AUNIP, RIPK1/3 He et al, 2016;Lee et al, 2016;Yang Z. et al, 2019 Prognostic NLRP3, MLKL, RIPK1/3, TLR3/TICAM1, AURKA Yuan et al, 2015;Yao et al, 2017;Conev et al, 2019;Soleymani Fard et al, 2019;Sun et al, 2019;Malhotra et al, 2020 Autophagy Diagnostic LC3, Na+/K+-ATPase, mTOR Mijatovic et al, 2012;Mete et al, 2018;Sui et al, 2018 Prognostic LC3, ATG, BECN1, Na + /K + -ATPase, AMPK, mTOR Cao et al, 2016;Cheng et al, 2016;Schläfli et al, 2016;Gajate et al, 2018;Guo et al, 2019 Ferroptosis Diagnostic GPX4, ALOX15, SLC7A11, BAP1, HSP90, HSPB1, FANCD2, TP53 Kamal et al, 2004;Guerriero et al, 2015;Saif et al, 2016;Hui et al, 2017;Davidson et al, 2018;Xu et al, 2019Prognos...…”
Section: Rcds Detection In Clinic Usagementioning
confidence: 99%
“…Some researchers have Karamitopoulou et al, 2007;Farnebo et al, 2011;Omori et al, 2011;Sen et al, 2015;Heng et al, 2016;Bani-Ahmad et al, 2018;Chen et al, 2019;Henrich et al, 2019;Moledina et al, 2019;Schiffmann et al, 2019 Prognostic Bcl-2, Bax, p53, Fas, FasL, caspase-2, caspase-3, caspase-7, caspase-8, caspase-9, TNF-α, DNA fragmentation, Bak, Bok, Bim, PUMA, PMAIP1, MCL1, BCL2L10, TRAIL, TRAIL-R1/2/3, c-FLIP, IAPs Feng et al, 2018;Huang K.H. et al, 2018 Necroptosis Diagnostic NLRP3, AUNIP, RIPK1/3 He et al, 2016;Lee et al, 2016;Yang Z. et al, 2019 Prognostic NLRP3, MLKL, RIPK1/3, TLR3/TICAM1, AURKA Yuan et al, 2015;Yao et al, 2017;Conev et al, 2019;Soleymani Fard et al, 2019;Sun et al, 2019;Malhotra et al, 2020 Autophagy Diagnostic LC3, Na+/K+-ATPase, mTOR Mijatovic et al, 2012;Mete et al, 2018;Sui et al, 2018 Prognostic LC3, ATG, BECN1, Na + /K + -ATPase, AMPK, mTOR Cao et al, 2016;Cheng et al, 2016;Schläfli et al, 2016;Gajate et al, 2018;Guo et al, 2019 Ferroptosis Diagnostic GPX4, ALOX15, SLC7A11, BAP1, HSP90, HSPB1, FANCD2, TP53 Kamal et al, 2004;Guerriero et al, 2015;Saif et al, 2016;Hui et al, 2017;Davidson et al, 2018;Xu et al, 2019Prognos...…”
Section: Rcds Detection In Clinic Usagementioning
confidence: 99%
“…The literature by García-Rojo et al [40] reported that CD3-, CD4-, and CD8- marker analysis may be used to distinguish between GERD and EoE patients. In rare situations, for example, children with strong clinical suspicion where fragments do not reach 15 intraepithelial eosinophils/HPF, immunostaining for arachidonate-15 lipooxygenase has been found to be a sensitive marker for EoE [84]. Moreover, von Arnim et al [85] reported 10 characteristic marker set (atopy, food impaction, dysphagia, PPI-refractory symptoms, peripheral eosinophilia, IgE, weight loss, painful swallowing/odynophagia, age, and sex) which effectively distinguish GERD from EoE.…”
Section: Comorbid Conditionsmentioning
confidence: 99%